Impact of JNK and Its Substrates on Dendritic Spine Morphology - Emilia Komulainen; Artemis Varidaki; Natalia Kulesskaya; Hasan Mohammad; Christel Sourander; Heikki Rauvala; Eleanor T. Coffey (MDPI, 2022)
The protein kinase JNK1 exhibits high activity in the developing brain, where it regulates dendrite morphology through the phosphorylation of cytoskeletal regulatory proteins. JNK1 also phosphorylates dendritic spine proteins, and Jnk1-/- mice display a long-term depression deficit. Whether JNK1 or other JNKs regulate spine morphology is thus of interest. Here, we characterize dendritic spine morphology in hippocampus of mice lacking Jnk1-/- using Lucifer yellow labelling. We find that mushroom spines decrease and thin spines increase in apical dendrites of CA3 pyramidal neurons with no spine changes in basal dendrites or in CA1. Consistent with this spine deficit, Jnk1-/- mice display impaired acquisition learning in the Morris water maze. In hippocampal cultures, we show that cytosolic but not nuclear JNK, regulates spine morphology and expression of phosphomimicry variants of JNK substrates doublecortin (DCX) or myristoylated alanine-rich C kinase substrate-like protein-1 (MARCKSL1), rescue mushroom, thin, and stubby spines differentially. These data suggest that physiologically active JNK controls the equilibrium between mushroom, thin, and stubby spines via phosphorylation of distinct substrates.